A new evolutionary optimization method for osteoporotic bone augmentation. Issue 7 (19th May 2017) - Santana Artiles, María E.; Venetsanos, Demetrios T.
Abstract : Bone augmentation is a preventative osteoporosis intervention, comprising the injection of bone cement into an osteoporotic bone. As injection of excessive amounts of bone cement may result into thermal necrosis of bone tissue or even embolism, the minimum cement volume required to achieve a predefined level of augmentation must be sought. To this end, the present paper introduces a new evolutionary optimization method, applicable to any osteoporotic bone. The method was numerically evaluated through a typical case of femoral augmentation and compared to another powerful optimization method. The results demonstrate the efficiency and low computational cost of the proposed method.